Older and wiser? Birth order and IQ of young men - Sandra E. Black; Paul J. Devereux; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2007)
While recent research finds strong evidence that birth order affects children's outcomes such as education and earnings, the evidence on the effects of birth order on IQ is decidedly mixed. This paper uses a large dataset on the population of Norway that allows us to precisely measure birth order effects on IQ using both cross-sectional and within-family methods. Importantly, irrespective of method, we find a strong and significant effect of birth order on IQ, and our results suggest that earlier born children have higher IQs. Our preferred estimates suggest differences between first-borns and second-borns of about one fifth of a standard deviation or approximately 3 IQ points. Despite these large average effects, birth order only explains about 3% of the within-family variance of IQ. When we control for birth endowments, the estimated birth order effects increase. Thus, our analysis suggests that birth order effects are not biologically determined. Also, there is no evidence that birth order effects occur because later-born children are more affected by family breakdown.
Keywords: 330; Kinder; Familie; Kognition; Norwegen